2023
DOI: 10.3390/nu15010237
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Attenuates Oxidative Stress and Inflammation via Mechanisms Involving Sirtuin-1 Activation and NF-κB Inhibition in Experimentally-Induced Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a stealthy disease, and its development is linked to mechanisms including inflammation and oxidative stress. Catalpol (CAT), an iridoid glucoside from the root of Rehmannia glutinosa, is reported to manifest anti-inflammatory, antioxidant, antiapoptotic and antifibrotic properties. Hence, we studied the possible nephroprotective effects of CAT and its mechanisms in an adenine-induced (0.2% w/w in feed for 4 weeks) murine model of CKD by administering 5 mg/kg CAT to BALB/c mice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The rest of the right and left kidneys were individually wrapped in aluminium foil and then dipped in liquid nitrogen and kept at −80 °C, pending analysis. The preparation of kidney homogenates for the quantification of markers of oxidative stress and inflammation were carried out as described earlier [ 28 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the right and left kidneys were individually wrapped in aluminium foil and then dipped in liquid nitrogen and kept at −80 °C, pending analysis. The preparation of kidney homogenates for the quantification of markers of oxidative stress and inflammation were carried out as described earlier [ 28 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Masson trichrome stains fibrous tissue blue. The percentage of blue-stained fibrotic area in each kidney section, stained with Masson trichrome stain, was evaluated and the fibrosis index was calculated and expressed as percentage according to the protocol previously reported [ 36 , 44 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The development of chronic kidney disease is associated with mechanisms such as inflammation and oxidative stress. It was shown that the 4‐week oral treatment of CKD mice with 5 mg/kg catalpol significantly improved the inflammatory response in the tissues of CKD mice without causing any harmful side effects (Zaaba et al, 2023). However, further research is needed if it is to be applied in the clinical setting.…”
Section: The Anti‐inflammatory Effects Of Catalpol In Various Diseasesmentioning
confidence: 99%
“…In summary, catalpol attenuates the inflammatory response in kidney injury by inhibiting the NF-κB signaling pathway.3.4.2 | Chronic kidney diseaseThe development of chronic kidney disease is associated with mechanisms such as inflammation and oxidative stress. It was shown that the 4-week oral treatment of CKD mice with 5 mg/kg catalpol significantly improved the inflammatory response in the tissues of CKD mice without causing any harmful side effects(Zaaba et al, 2023). However, further research is needed if it is to be applied in the clinical setting.3.4.3 | Diabetic nephropathy (DN)DN is one of the most common complications of diabetes and a major cause of end-stage kidney disease, the pathogenesis is still unclear, and current studies have shown that it is closely related to foot cell injury, microcirculatory dysfunction, inflammatory response, and oxidative stress(Elmarakby & Sullivan, 2012;Umanath & Lewis, 2018;Wada & Makino, 2013).…”
mentioning
confidence: 99%
“…Histologically, CAT demonstrates notable effects in reducing tubular necrosis, interstitial fibrosis, and dilation in the kidney. The beneficial effects of CAT against adenine-induced CKD in mouse models involve mechanisms such as sirtuin-1 activation and NF-κB inhibition [74].…”
mentioning
confidence: 99%